2021
DOI: 10.18632/aging.203724
|View full text |Cite
|
Sign up to set email alerts
|

Increased proliferation and differentiation capacity of placenta-derived mesenchymal stem cells from women of median maternal age correlates with telomere shortening

Abstract: Mesenchymal stem cells (MSCs) experience functional decline with systemic aging, resulting in reduced proliferation, increased senescence, and lower differentiation potential. The placenta represents a valuable source of MSCs, but the possible effect of donor age on the properties of placenta-derived mesenchymal stem cells (PDMSCs) has not been thoroughly studied. Thus, the aim of this study was to underscore the effect of maternal age on the biological characteristics and stemness properties of PDMSCs. PDMSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…It also provided space for telomerase to bind to telomere DNA, resulting in telomere elongation and mESC proliferation ( Figure 6 ). Telomere length maintenance is important to facilitating cell division [ 35 ], which is also critical for the unlimited self-renewal, pluripotency and chromosomal stability of mESCs [ 36 ]. The risk of diseases associated with a reduced cell proliferation, including aging or aging-associated diseases, is correlated with an increase in the shortening of telomeres [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also provided space for telomerase to bind to telomere DNA, resulting in telomere elongation and mESC proliferation ( Figure 6 ). Telomere length maintenance is important to facilitating cell division [ 35 ], which is also critical for the unlimited self-renewal, pluripotency and chromosomal stability of mESCs [ 36 ]. The risk of diseases associated with a reduced cell proliferation, including aging or aging-associated diseases, is correlated with an increase in the shortening of telomeres [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This overexpression of β5 not only enhanced the stemness and proliferative capacity of late-passaged MSCs, but it also resulted in a decrease in proteasomal oxidative protein modifications and intracellular ROS levels ( Kapetanou Marianna et al, 2017 ). Furthermore, it has been demonstrated that the ability of MSCs to form colonies is also influenced by telomere length ( Guerrero et al, 2021 ) and the consistent expression of proto-oncogenes, such as B cell lymphoma 3 (Bcl-3) ( Wang Fuxiao et al, 2022 ).…”
Section: Characteristics Of Mscs Senescencementioning
confidence: 99%
“…The efficacy of osteogenic differentiation of MSCs isolated from adults is diminished compared to MSCs isolated from children [ 150 ], suggesting that MSCs undergo aging in vivo. The proliferative potential of MSCs in culture is limited and close to the margin determined by Hayflick [ 151 ], and telomere shortening is due to cellular divisions rather than other age-related processes [ 152 ]. Telomerase activity in MSCs is low or altogether absent [ 108 , 153 , 154 ], and its varying level may be due to the heterogeneity of MSC populations [ 155 ].…”
Section: Replicative Senescence In Different Types Of Stem Cellsmentioning
confidence: 99%